Parenting style and emotional intelligence as the predictors of academic buoyancy among the senior secondary students - Singh, Sarab Tej; Kumar, Satish; Singh, Vishal (Journal of Education and Learning (EduLearn), 2025)
The current research is the study of academic buoyancy in relation to emotional intelligence and parenting styles. Academic buoyancy is a strength in a student’s life to deal with the routine problems in classroom study like low grades, negative feedback by teachers, and difficulties in understanding of concepts. For the studying the relationship between the variables, data was collected from the various school of Punjab state. The data of 1,149 students were used for the analysis. The results of the research explained that academic buoyancy and emotional intelligence of the girls was found to be significantly higher than boys. Among the four parenting styles there was also gender difference. Furthermore, on the basis of stream, there was a significant difference in all the variables. In correlation analysis, there was a significant relationship between academic buoyancy and emotional intelligence. Moreover, findings of the research revealed that, both emotional intelligence and parenting styles were found to be significant predictors of academic buoyancy. So, this research is very helpful for the parents, school principals, policymakers, and administrators.